The Effect of Critical Multiliteracy Learning Model on Students' Reading Comprehension - Siti Maesaroh; Mumu Muzayyin (Qualitative and Quantitative Research Center, 2022)
This study aims to determine the influence of the Critical Multiliteracy model on the reading comprehension ability of fifth graders at State Elementary School (SDN) 1 Majasem. The approach used in this research is quantitative. The research design used was a one-group pretest-posttest design. The population was the fifth-grade elementary school at SDN 1 Majasem. The sample of this research is 24 students. The data collection technique in this study used a test in the form of multiple choice questions and a description of 20 questions. The research data were analyzed using normality, homogeneity, and t-test. Based on the study's results, it is known that the multiliteracy learning model has a significant effect on students' reading comprehension skills. This result can be seen from the significance value is 0.013 < 0.05. Thus, the critical multiliteracy learning model positively impacts students' reading comprehension skills.